Detection of Free Living Amoeba infection in patients with suspected central nervous system and keratitis disease in Shiraz, southern Iran - Mohammad Saleh Bahreini; Mohammad Hossein Motazedian; Shahram Bamdad; Mohammad Javad Abbaszadeh afshar; Qasem Asgari (Shiraz University of Medical Sciences, 2019)
Background:Free Living Amoebas, as opportunistic protozoa, can cause more problems such as meningoencephalitis, encephalitis and keratitis in human being. These protozoa have been isolated from many sources in Iran. This study was undertaken to determine the diseases due to these parasites in the south of Iran. Methods: In this cross-sectional study, 200 cerebrospinal fluid (CSF) samples and 15 corneal scrapings were collected from patients admitted in clinics of Shiraz city. The samples were examined by light microscopy, cultivation and molecular methods. Phylogenetic relationship was also conducted among the sequences and various Acanthamoeba spp. based on nucleotide sequences in NCBI GenBank. Results: No infection in CSF samples was seen, while one patient suspected with keratitis was positive to Acanthamoeba sp. infection only by PCR. Using Sequencing technique and Phylogenetic tree, the genotype of the parasite was demonstrated T4. This sample belonged to a 26 year old woman who used a contact lens. Conclusion: Our results indicate that it is necessary to pay attention to the complexity of the free living amoeba infections, especially in soft contact lens wearers. Also, PCR as an appropriate method in diagnosis is recommended for the detection of free living amoebae. However, it is unavoidable to suspect these protozoa as an infectious agent in patients with central nervous system infection due to increased immunodeficiency disorders.